AN UNJUST INTERPRETATION OF SECTION 116(1) OF THE CONSUMER PROTECTION ACT 68 OF 2008: THE IMPACT OF First Rand Bank Limited v Ludick GP (unreported) 2020-06-18 Case no A277/2019 - Tshepiso Scott-Ngoepe (Obiter, 2024)
One of the key objectives of the Consumer Protection Act (68 of 2008) (CPA) is to ensure that consumers are provided with “an accessible, consistent, harmonised, effective and efficient system of redress”. This has not been an easy feat. Some difficulties have arisen from the interpretation of a detailed, yet unclear system of redress as set out in section 69 of the CPA, particularly in relation to when the court can be approached and whether there is an implied hierarchy that applies in the dispute resolution process. In other instances, the reluctance of industry members to willingly co-operate with accredited industry ombuds has made the work of these dispute resolution agents challenging. A further aspect that has undermined a key objective of the CPA to ensure that consumers have access to redress, is the interpretation that has been afforded to section 116(1) of the CPA, following the decision of the High Court in FirstRand Bank Limited v Ludick (unreported case no: A277/2019). Section 116(1) of the CPA regulates prescription in terms of the statute. It provides that consumers ought to approach the consumer court or Tribunal within a period of three years from the date of the act or omission; or, in the case of conduct that is ongoing or continuing, the date upon which, the conduct in question ceased. Before Ludick, the Tribunal adopted a less stringent approach to this provision. Following Ludick, however, the approach of the Tribunal in CPA-related matters concerning the interpretation of section 116(1) of the CPA changed— arguably for the worst. In light of this, this note analyses the decision in Ludick and its application over the past few years to CPA prescription matters. This discussion is prefaced by a discussion of the facts and the finding of Ludick.  This is followed by a critical discussion of the court’s prescription-related findings, which assesses: (i) the nature of the matters adjudicated under the NCA and the CPA respectively; (ii) the Tribunal’s powers; (iii) the adverse impact of Ludick on the Tribunal’s interpretation of section 116(1) of the CPA; and (iv) a constitutionally aligned interpretation of section 116(1) of the CPA.